The effect of Storytelling Marketing on consumer purchasing decisions: Field and analytical research on a sample of Turquoise customers - Abdul Razzaq, Noor Qusay (Journal of Economic, Administrative and Legal Sciences, 2022)
The aim of the research is to determine the extent of the impact of Storytelling Marketing on consumer purchasing decisions and the type of relationship between them. The research problem was embodied by asking questions, the most important of which were: Do demographic factors affect consumer purchasing decisions?, and is there an impact and correlation of Storytelling Marketing on consumer purchasing decisions? Turquoise Company was chosen as a research community because of its renewable presentation and its adoption of narrative marketing in presenting its products. The research also relied on the descriptive and analytical method for data presentation and analysis. SPSS program (V.23) was used to analyze the data using statistical methods (Pearson correlation coefficient, simple regression analysis method, and F, t test). One of the most important conclusions reached by the research: Demographic factors affect consumer purchasing decisions. Storytelling Marketing contributes to influencing purchasing decisions. As for the most important recommendations made by the research: the need for the company to adopt methods of reducing additional costs and to clarify this when presenting its storytelling marketing because of its impact on the purchasing decisions of the consumer.
Keywords: Storytelling Marketing; consumer purchasing decisions; company